2014
DOI: 10.5430/jbgc.v5n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Nephrostomy in pregnancy a district general hospital experience over five years

Abstract: Background: Obstructed kidney is also termed hydronephrosis. An obstructed kidney produces buildup of urine within the kidney which increases pressure within the kidney. This condition can be a result of several different causes of which pregnancy is one of them. Obstructed kidneys in pregnancy call for relieving by nephrostomy which is a thin, plastic tube (catheter) that is inserted through the skin on the back and into the kidney. It can relieve a build-up of urine in the kidney and prevents the kidney from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Numerous studies have demonstrated the effectiveness and reliability of PCN placement in the general population; nonetheless, only a few studies with a limited number of patients have reported the effectiveness of ultrasound-guided PCN placement in pregnant women 10,11 Several published studies have reported data from sample sizes ranging between 1 and 52 on the application of PCN placement during pregnancy; however, a combination of fluoroscopy and ultrasound was frequently utilized in these studies [1][2][3]12 . The potential adverse effects of radiation on the fetus are well established 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated the effectiveness and reliability of PCN placement in the general population; nonetheless, only a few studies with a limited number of patients have reported the effectiveness of ultrasound-guided PCN placement in pregnant women 10,11 Several published studies have reported data from sample sizes ranging between 1 and 52 on the application of PCN placement during pregnancy; however, a combination of fluoroscopy and ultrasound was frequently utilized in these studies [1][2][3]12 . The potential adverse effects of radiation on the fetus are well established 1 .…”
Section: Discussionmentioning
confidence: 99%
“…It usually presents as a mild condition and is generally accepted as a physiological process 1 . Factors such as the pressure of the uterus, iliac artery, or dilated uterine veins on the ureter, reduction in ureteral smooth muscle peristalsis due to hormonal effects, and the presence of kidney stones are considered potential etiological factors for pregnancy-related hydronephrosis 2 . While the majority of physiological hydronephrosis cases remain asymptomatic, it can progress in some instances, resulting in symptoms such as flank pain, hematuria, proteinuria, acute kidney failure, and severe urinary tract infections 1,2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 2 patients had blocked nephrostomies, whereas 2 patients had nephrostomies that fell out. [46] There was an instance of infection that required oral antibiotics in one of the patients. Similar to ureteric stent, nephrostomy encrustation is an issue.…”
Section: Stentmentioning
confidence: 99%
“…Different techniques can be used for insertion of PCN. The most commonly used techniques are either Seldinger's technique which include puncture of kidney by a needle then insertion of guide wire and dilatation over this wire to form a wide track enough for passage of nephrostomy catheter or one-stab technique (Bonnano Technique) using a pigtail Teflon catheter mounted on a hollow 18G needle which has a sharp beveled edge to be directly inserted in the pelvicalyceal system (3). PCN insertion can be either under ultrasound (US) guidance or combined US and fluoroscopy guidance.…”
Section: Introductionmentioning
confidence: 99%